Prevalence of polycystic ovary syndrome in patients with type 2 diabetes: A systematic review and meta-analysis - Long, Caiyi; Feng, Haoyue; Duan, Wen; Chen, Xin; Zhao, Yuemeng; Lan, Ying; Yue, Rensong (Frontiers in Endocrinology, 2022)
Purpose: With type 2 diabetes mellitus (T2DM) occurring at a younger age, a greater number of women with T2DM experience reproductive health problems. The prevalence of polycystic ovary syndrome (PCOS), a common reproductive disease associated with T2DM, remains unknown in women with T2DM. This systematic review and meta-analysis aimed to determine the prevalence of PCOS in women with T2DM. Methods: Stata 15.1 was used to perform a meta-analysis on the prevalence of PCOS in patients with T2DM included in this study. Additionally, a narrative review of the effects of different diagnostic methods, obesity, state, and other factors on the prevalence of PCOS was conducted. Results: Meta-analysis showed that the overall prevalence of PCOS in women with T2DM was approximately 21%. Subgroup analysis showed that the incidence of PCOS in female patients aged 25-45 years was higher than that in female patients aged < 25 years. The prevalence of PCOS in obese women was 14%, which was lower than that in normal weight women and normal weight or overweight or obese women. Women with T2DM in Oceania had the highest incidence of PCOS, followed by those in Europe and Asia; women with T2DM in North America had the lowest incidence. In terms of PCOS diagnostic standards, the prevalence of PCOS diagnosed by the National Institutes of Health was the lowest. The prevalence of PCOS diagnosed on the basis of clinical symptoms and biochemical characteristics was the highest, and the prevalence of PCOS diagnosed on the basis of medical records was 20%. Conclusions: PCOS is a common disease in female patients with T2DM. The prevalence of PCOS in women with T2DM at childbearing age was higher than that in adolescent females. Women with T2DM at childbearing age should pay attention to the screening and prevention of PCOS to avoid the hazards of PCOS to reproductive health.